DBASE SOFTWARE APPLICATIONS FOR DATA PROCESSING IN THE CAR RENTAL PT. DUABE - Eka Barlian Syah; Irfan Irfan, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Basically every rental is a work unit which has functions to collect, maintain, and utilize the rental car which was then given to service users. One of the factors that influence for an establishment engaged in the rental is the number of cars that want to use. because the number of stock cars that will be rented out, will greatly assist these efforts in meeting the needs of tenants. Another factor that also influences is how or tools that strongly support the speed and processing research data, transactions and the calculation of complex data on these enterprises, given the increasingly sharp competition berkembangan rental car today. Delays in producing reports that are treated, both on the vehicle, the tenant or transaction is the most common problem encountered in the car rental business. damage or loss of a device resulted in changes to the report of a bundle, not in the days of its existence because at some point will be damaged or missing.